ANEMIA OF PREGNANCY ASSESSED FROM THE COMPLIANCE BEHAVIOR OF PREGNANT WOMEN IN CONSUMING IRON SUPPLEMENTS IN THE WORKING AREA OF PITU HEALTH CENTER, NGAWI DISTRICT - Kurniasih, Erwin (Universitas Airlangga, 2021)
Introduction: pregnant women with anemia are at high risk of bleeding which can cause serious complications to both the mother and the fetus. In Indonesia, maternal mortality due to bleeding due to anemia is quite high because many pregnant women disobidient to consume iron supplements. The study was to determine the relationship between the obedience behavior of pregnant women in consuming iron supplements with the incidence of pregnancy anemia in the working area of the Pitu Community Health Center, Ngawi Regency. Methods: This study used a cross sectional design and total sampling of 60 respondents. The data collection method was using a questionnaire and analyzed by using the Chi Squre test. Results: The results showed 18 respondents (30%) were at a high level of adherence with anemia condition 5 people (8.3%). Respondents with a moderate level of adherence were 34 people (56.7%) with anemia conditions 16 people (26.7%), and 8 respondents (13.3%) had a low level of compliance with anemia. The statistical test results obtained p value = 0.003 (p <0.05). Conclusion: There is a relationship between compliance behavior of pregnant women in consuming Fe supplements with the incidence of pregnancy anemia